STUDY ON DYNAMIC BENDING CHARACTERISTICS OF WOVEN CARBON FIBER COMPOSITE MATERIAL REINFORCED ALUMINUM ALLOY CAP THIN⁃WALLED BEAMS - CHEN Guang; YANG YuJie; HAN Duo; LIU Ye; JING GuoXi (Jixie qiangdu)
The metal/composite hybrid thin⁃walled structure can meet requirements of both crashworthiness and light⁃weight of auto body.Intended to compare the dynamic bending characteristic of Al/CFRP(Aluminum/Carbon Fibre Reinforced Plastic)hybrid beams with different fiber layup patterns,the bending failure behavior and crashworthiness of specimens were comparatively analyzed by three⁃point bending tests,and the finite element model was established in good agreement with experimental results.On this basis,the effects of punch size,punch shape and impact position on the bending performance of the hybrid beam were further analyzed.The results show that layup angle has a greater effect on the bending performance than the layup sequence.The larger the punch size,the flatter the punch shape or the further away from the middle the impact position is,the better the crashworthiness characteristic is.These methods used and these obtained conclusions can provide a reference for the crashworthiness design of similar bending resistant structures.